Graded exercise with motion style acupuncture therapy for a patient with failed back surgery syndrome and major depressive disorder: a case report and literature review - Kim, Do-Young; Ha, In-Hyuk; Kim, Ju-Yeon (Frontiers in Medicine, 2024)
Effective treatment of failed back surgery syndrome (FBSS) remains challenging despite urgent medical attention requirements. Depression is a contributing factor to the development and poor prognosis of FBSS, and vice versa. We report the case of a patient with FBSS and major depressive disorder (MDD) treated with graded exercise combined with motion-style acupuncture therapy (MSAT). A 53-year-old male veteran who had undergone lumbar discectomy and laminectomy with instrumented fusion was admitted to the hospital with re-current back pain and radiative pain in the left leg. The effects of failed surgery triggered MDD as a comorbidity. After a six-week routine treatment without remarkable improvement, a three-week program of graded exercise with MSAT was applied. The numeric rating scale (NRS) and short form-36 (SF-36) were used to assess low back pain with radiating leg pain, and daily functioning levels, respectively. The voluntary walking distance of the patients was measured. To analyze the therapeutic effects and other applications of the intervention, we surveyed clinical trials using MSAT or graded exercise therapy (GET). Three weeks of graded exercise with MSAT reduced physical and mental functional disabilities (SF-36, physical component: 15.0 to 37.2, mental component: 21.9 to 30.1) as well as the intensity of low back pain and/or radiative leg pain (NRS: 50 to 30). Furthermore, as the therapeutic intensity gradually increased, there was a significant corresponding increase in daily walking distance (mean daily walking distance, the first week vs. baseline, second, and third week, 3.05±0.56 : 2.07±0.79, 4.27±0.96, and 4.72±1.04 km, P=0.04, P=0.02, and P=0.003, respectively). Three randomized controlled trials of GET were included, all showing statistically significant antidepressant effects in the diseased population. Graded exercise with MSAT may be an effective rehabilitative therapy for patients with FBSS and MDD who have impaired daily routines.